Resting and postprandial serum bile acid concentrations in dogs with liver disease. (6th May 2021) - Pena‐Ramos, Jorge; Barker, Lucy; Saiz, Rocío; Walker, David J.; Tappin, Simon; Hare, Cassia H. Z.; Roberts, Madeleine L.; Williams, Tim L.; Bexfield, Nicholas
Abstract: Background: Serum bile acids (SBAs) are frequently measured in dogs. However, there is limited data comparing SBAs in different liver diseases diagnosed according to standardized histological criteria. Objectives: To compare resting and postprandial SBAs, and determine their sensitivity and specificity, for various liver diseases in dogs. Animals: Three hundred and forty‐one client‐owned dogs with suspected liver disease that had a liver biopsy and SBAs measured. Methods: Multicenter retrospective study. Cases were classified according to standardized histological criteria. The sensitivity and specificity of resting and postprandial SBAs for the diagnosis of each liver disease, and all liver diseases combined, were calculated. Results: The median resting SBAs were highest in dogs with cirrhosis (98.8 μmol/L; range, 6‐135) and congenital circulatory anomalies (CCa; 79.45 μmol/L; 0.3‐705). The highest median postprandial concentrations were found in CCa (126 μmol/L; 0‐726) and chronic hepatitis (CH; 54.3 μmol/L; 0‐260). Using the cut‐off value of 10 μmol/L, the highest sensitivities of resting SBAs were recorded in dogs with CCa (87.5%; 95% confidence interval, 76.8‐94.4) and CH (81.1%; 71.5‐88.6). The sensitivities of postprandial SBAs were the highest in cholangitis (100%; 47.8‐100.0) and CCa (91.1%; 78.8‐97.5). The specificities of resting and postprandial SBAs for all diseases were 49.3% (37.6‐61.1) and 29.7% (15.9‐47.0), respectively. Conclusions and Clinical Importance: Postprandial SBAs are more sensitive but less specific than resting SBAs for the diagnosis of liver disease. There were dogs in all categories of liver disease with resting SBAs <10 and >90 μmol/L. Therefore, careful interpretation of both normal and elevated values is required.